PEMANFAATAN TUMBUHAN ECENG GONDOK ( Eichhornia crassipes ) DAN IMPLIKASINYA TERHADAP KETAHANAN EKONOMI KELUARGA (Studi di Desa Kalangbancar, Kecamatan Geyer, Kabupaten Grobogan, Propinsi Jawa Tengah ) - , Wiranto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research was carried out in Kalangbancar village, Geyer sub-regency, Grobogan regency, Central Java province in 2010. The goal is to find out the effect of water hyacinth use on family economic resilience and the better use of water hyacinth processing. The method in use is descriptive qualitative method. The population consists of 66 people who process the water hyacinth. The sample in use is purposive sampling. The data collected through observation and interview. The device of research in use is questionnaire list. The result shows that water hyacinth use in Kalangbancar village gives significance contribution to the people of the village and water hyacinth craftmen in enhancing income and family economic earning of the respondents. The water hyacinth use also keep the river clean of the water hyacinth polution, keep the river becoming shallow and flood, and give the Kalangbancar village people new jobs. The water hyacinth processed by the people of Kalangbancar village only with simple and natural devices. This process show a positive effect on family economic resilience, the proof shows the enhancement of respondentâs family income. The family of the respondents show the amount of 93.94 percents beyond poverty line by Sajogyo of 100 percent of village area by Central Java province BPS, therefore they catogorized into non-poor groups. It concludes that the water hyacinth use has positive effect on the respondentâs family economic resilience. The economic resilience of the respondent family enhances through water hyacinth use into various products such as handicraft favored by local or international market.